Adductor Canal Block Does not Confer Better Immediate Postoperative Pain Relief after Total Knee Arthroplasty - Padki, Akshay; Vemula, Vishnu; Purnomo, Glen; Lim, Jason Beng Teck; Liow, Lincoln Ming Han; Yeo, Seng Jin; Chen, Jerry Yongqiang (The Journal of Knee Surgery, 2022)
The adductor canal block (ACB) is a useful adjunct to control postoperative pain in total knee arthroplasty (TKA). The aim of our study was to compare postoperative day 1 (POD1) pain scores, ambulation distance, range of motion, active straight leg raise (SLR), and length of stay (LOS) in TKA patients receiving no ACB (NACB), ACB by surgeon (ACBS), or ACB by anesthetist (ACBA). After obtaining institutional ethics approval, a retrospective review of 135 patients who underwent TKA between September 2020 and March 2021 was performed. All patients underwent TKA by the same surgeon and received the same standardized postoperative rehabilitation. Operating theater time was shortest in the NACB group with 129.3 ± 23.1 minutes compared with 152.4 ± 31.6 minutes in ACBA and 139.2 ± 29.4 minutes in ABCS (p = 0.001). For the POD1 pain score after therapy, the NACB group scored 4.9 ± 3.1 compared with 3.5 ± 2.2 and 3.9 ± 1.8 scored by the ACBA and ACBS groups, respectively (p = 0.302). The mean POD1 ambulation distance was 21.1 ± 15.2 m in the NACB group compared with 15.4 ± 1.3 and 17.8 ± 13.2 m in the ACBA and ACBS groups (all p > 0.05), respectively. There were no significant differences in the median LOS between three groups or ability to perform active SLR (all p > 0.05). Our study found no significant differences when comparing ACBS and ACBA by POD1 pain score, ambulation distance, range of motion, and LOS. We recommend against the use of ACB and instead recommend surgeons to perform an adequate periarticular cocktail injection.
Keywords: adductor canal block; total knee arthroplasty; enhanced recovery; analgesia; postoperative pain